PENEMUAN HUKUM HAKIM MAHKAMAH KONSTITUSI DALAM PUTUSAN MAHKAMAH KONSTITUSI NOMOR 21/PUU-XII/2014.MK KASUS PROYEK BIOMEDIASI PT.CHEVRON BACHTIAR ABDUL FATAH - Suratno, Ujang (Yustitia, 2018)
Judicial authority in Indonesia is carried out by a Supreme Court and the Constitutional Court which has the authority to examine laws against the 1945 Constitution of the Republic of Indonesia and decide on the authority dispute of state institutions whose authority is granted by the 1945 Constitution of the Republic of Indonesia. The Constitutional Court in examining the Law against the 1945 Constitution became a polemic related to the prejudicial object which was finally answered through the decision of the Constitutional Court (MK) number 21 / PUU-XII / 2014. The Constitutional Court granted part of the application for corruption convictions in the case of PT Chevron Bachtiar's Abdul Fatah biomediation project, one of which examined the prejudicial object provisions which were polemic, especially after the South Jakarta District Court's prejudicial has canceled the status of suspect Commissioner Budi Gunawan (BG) by the KPK. This study is a legal research using a normative juridical approach and descriptive analytical research specifications. The data used in this study are secondary data consisting of primary, secondary and tertiary legal materials. Data obtained through library studies and field research in the form of legislation, books, journals, and authoritative electronic media. The results of this study are 2 (two) explanations, namely First, Constitutional Court Judges have made legal inventions by providing interpretations and limitations on what can be the object of prejudicial in criminal procedural law by testing it against the constitution and seeing whether the KUHAP Articles tested are contradictory with constitutional rights. Secondly, the Constitutional Court uses several interactive techniques used by member judges in decision number 21 / PUU-XII / 2014. In the joint decision, the judges used Authentic, Systematic, Grammatical, Historical, Extensively and sociological interpretation techniques. This can be seen in the decision of point one stating a phrase which means interpreting the law using grammatical techniques